Spanish version of the Frontotemporal Dementia Knowledge Scale: adaptation and validation - Guimet, Nahuel Magrath; Calandri, Ismael Luis; Bagnati, Pablo Miguel; Wynn, Matthew; Allegri, Ricardo Francisco (Arquivos de Neuro-Psiquiatria, 2022)
Background: Frontotemporal dementia (FTD) is a neurodegenerative disease and is one of the most common causes of dementia in people under 65. There is often a significant diagnostic delay, as FTD can be confused with other psychiatric conditions. A lack of knowledge regarding FTD by health professionals is one possible cause for this diagnostic confusion. Objectives: The aim of this study was to adapt and validate the Frontotemporal Dementia Knowledge Scale (FTDKS) in Spanish. Methods: A translation was done, following cross-cultural adaptation guidelines, which consisted of forward translation, blind back translation, and an analysis by a committee of experts. For the present study, 134 professionals from different health areas responded the Spanish version of the FTDKS. The statistical analysis was performed using R version 4.0.0 “Arbor day” and the Psych, sjPlot packages. Results: The Spanish version of the FTDKS had good reliability and internal consistency (Cronbach alpha 0.74.). The sample's mean score was 19.78 (range = 4-32, SD 6.3) out of a maximum of 36 points. Conclusions: The results obtained show that the Spanish version has good psychometric properties. The FTDKS is applicable in our environment and can be a useful tool to evaluate the knowledge of health professionals regarding frontotemporal dementia.
Keywords: Frontotemporal Dementia; Frontotemporal Lobar Degeneration; Aphasia; Dementia; Diagnostic Errors; Neuropsychiatry